Management and Mitigation of Acid Mine Drainage in South Africa : Input for Mineral Beneficiation in Africa - Mutanga, Shingirirai Savious; Mujuru, Munyaradzi (Book collections on Project MUSE., 2017)
South Africa is facing the increasing challenge of acid mine drainage (AMD) whose genesis is the country's mining history, which paid limited attention to post-mining mine site management. In mineral resource-rich Africa, this has emerged as one of the most daunting challenges of our time. South Africa has been bold in its approach to mitigating this problem, although the challenge is multi-faceted. On a positive note, substantial research has been conducted to confront the challenge. However, thus far, the research has been largely fragmented. This book builds on the work that has been done, but also provides a refreshing multi-disciplinary approach that is useful in addressing the AMD challenges that South Africa and the continent face. Whilst addressing the problem as a scientific and engineering challenge, the book also exposes the economic, policy and legal challenges involved in addressing the problem. The book concludes, quite uniquely, that AMD is an opportunity that can be used by South Africa and Africa to solve problems, such as acute water shortage, as well as mineral recovery operations.